The concept of social capital in disaster management - Mohd Khalid, Norhadizah; Abu Bakar, Elistina; Sulaiman, Norhasmah; Sabri, Mohamad Fazli (Academic Inspired Network, 2018)
This paper elucidates the concept of social capital of bonding, bridging and linking in disaster management. The elements in social capital of social cohesion and social networking are delineated and simultaneously the elements of trust to top management, participation and collaboration in disaster preparedness are elaborated.